Anxiety-like responses induced by nitric oxide within the BNST in mice: Role of CRF1 and NMDA receptors - Faria, M. P. [UNESP]; Miguel, T. T.; Gomes, K. S. [UNESP]; Nunes-de-Souza, Rl. [UNESP] (Elsevier B.V., 2016)
It has been shown that the bed nucleus of the stria terminalis (BNST) of rats contains nitrergic neurons, which are activated during animal exposure to aversive stimuli. The BNST is also populated by glutamatergic and corticotrophin releasing factor (CRFergic) neurons, which in turn are activated under stressful situations. Here we investigated the anxiogenic-like effects of intra-BNST injections of a nitric oxide (NO) donor, NOC-9 in mice. The role of CRFergic and glutamatergic systems on defensive behavior induced by NOC-9 was investigated with previous intra-BNST infusion of different doses of CP376395, a CRF type 1 receptor antagonist (CRF1), or AP-7, an NMDA (N-methyl-D-aspartate) receptor antagonist. Anxiety-like behavior was assessed immediately and 5 min after intra-BNST drug injection, exposing mice to a novel arena and to the elevated plus-maze (EPM; an anxiogenic situation). Results showed that NOC-9 provoked a short period (approximate to 150 s) of freezing behavior in the novel arena and increased anxiety in the EPM. Both CP and AP-7 attenuated the anxiogenic-like effects of NOC-9 in the EPM without changing freezing behavior in the novel arena. When given alone (i.e. without prior intra-BNST injection of NOC-9), AP-7 (0.20 nmol), but not CP (0.75, 1.50, or 3.00 nmol), attenuated anxiety in mice exposed to the EPM. These results suggest that CRF1 and NMDA receptors located within the BNST differentially modulate aversive effects induced by NO production in this limbic forebrain structure. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Bed nucleus of the stria terminalis; Nitric oxide; Freezing; Anxiety; CRF1 and NMDA receptors; Mice